2022
DOI: 10.1192/j.eurpsy.2022.2302
|View full text |Cite
|
Sign up to set email alerts
|

Improving treatment of patients with psychosis in low-and-middle-income countries in Southeast Europe: Results from a hybrid effectiveness-implementation, pragmatic, cluster-randomized clinical trial (IMPULSE)

Abstract: BackgroundIn Southeast Europe (SEE) standard treatment of patients with psychosis is largely based on pharmacotherapy with psychosocial interventions rarely available. DIALOG+ is a digital psychosocial intervention designed to make routine care therapeutically effective. This trial simultaneously examined effectiveness of DIALOG+ versus standard care on clinical and social outcomes (Aim 1) and explored intervention fidelity (Aim 2). MethodsA hybrid type II effectiveness-implementation, cluster randomised trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
(48 reference statements)
1
4
0
Order By: Relevance
“…Time horizon for the economic evaluation was 6 months, starting from implementation of the intervention at baseline. This was consistent with the time horizon for the effectiveness evaluation of DIALOG+ in the IMPULSE trial [14].…”
Section: 5 Economic Evaluationsupporting
confidence: 81%
See 4 more Smart Citations
“…Time horizon for the economic evaluation was 6 months, starting from implementation of the intervention at baseline. This was consistent with the time horizon for the effectiveness evaluation of DIALOG+ in the IMPULSE trial [14].…”
Section: 5 Economic Evaluationsupporting
confidence: 81%
“…In this trial, we observed modest improvements of quality of life measured by three instruments. Only the difference in MANSA scores (i.e., the primary clinical effectiveness outcome in the IMPULSE trial) between the intervention and control groups was statistically significant [14]. The primary economic evaluation relied on QALYs derived from the EQ-5D-5L data as the outcome measure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations